Halal Cosmetics in India : Analysis of the business opportunity for Spanish companies - De Pablo Cabrera, Alejandro; Sánchez-González, Pilar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Based on the need for business to growth, this research analyzes the potential of Indian market for Spanish companies in the cosmetics sector. A review of the literature has been carried out, specifically focused on the historical relationship between cosmetics and Islam. The productive capacity of Spain for cosmetic products has been assessed and, finally, the HALAL BRAND concept has been addressed since India is the world's leading cosmetic market for this type of product. The results corroborate the proposed hypotheses.